Cerebral Edema Associated with Ventricular Reservoirs in Two Patients: A Case Report. (26th February 2012) - Cress, Marshall C.; Spurgeon, Angela N.; Miller, Douglas C.; Litofsky, N. Scott
Abstract : Placement of ventricular reservoirs is a common practice to treat various tumors of the central nervous system (CNS). Ventricular catheter-reservoir-associated edema has been noted in the literature, but a thorough review of this literature identified no articles that examine this particular complication in neurooncology patients, specifically. We report two cases of ventricular catheter-reservoir-associated edema in patients receiving treatment for CNS metastasis.